PECULARITIES OF CONTEMPORARY PERSONALL TRAINING FOR SEARCHES OF MINERALS IN INSTITUTES OF HIGHER EDUCATION OF UKRAINE - GRINCHENKO, V.; PANOV, B.; FEDOTOVA, L. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Questions of features and conditions of a professional training in branch of searches of minerals in higher educational institutions of Ukraine at a modern level are covered. The attention is stressed on defects of existing system and some ways of its improvement are offered.